Ten-cusped primary molar tooth: A rare entity with literature review - Jose, EJ Akhil (J Oral Maxillofac Pathol, 2020)
Teeth arise by complex and progressive interactions between the ectoderm, oral epithelium and underlying mesenchyme. However, it may show variations and changes in morphological structure. A 6-year-old female child patient came for the treatment of her carious tooth. Intraoral examination revealed supernumerary cusp on occlusal surface of the maxillary right second primary molar. Incidence of supernumerary cusp is a rare condition formed by abnormal proliferation and folding of inner enamel epithelium during morphodifferentiation stage of the tooth development. Conservative cavity preparation and restorative treatment protocol were carried out to treat this case. Early diagnosis, management and timely recall of these rare anomalies will help to avoid potential complications, resulting from faster carious progression in these teeth due to the presence of many fissures and early pulpal extensions into the cuspal area.